ANALISIS PARTISIPASI AKTIF SISWA MELALUI KEGIATAN PEMBUATAN POSTER KESEPAKATAN KELAS PADA PEMBELAJARAN PPKN - Bagas Priyambodo; Natasya Megumi; Nova Noer Cahyani; Deni Zein Tarsidi (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze students’ active participation through the activity of creating a classroom agreement poster in Civics Education. The study was conducted in an elementary school in Sukoharjo with students of IV as the research subjects. The method used was descriptive qualitative through observation, interviews, and documentation. The results indicate that the activity of creating a classroom agreement poster can increase students’ active participation, as seen in their involvement in discussions, expressing opinions, collaborating in groups, and taking responsibility for the assigned tasks. In addition, students began to show discipline and awareness of the agreed rules. However, several obstacles were still found, such as some students being passive and lacking confidence in expressing their ideas. Therefore, the teacher’s role is important in providing guidance, motivation, and creating an inclusive and supportive classroom environment.